Study on disaster-causing probability evaluation of gas pipeline in karst area. - Qiaochu Li; Peng Zhang (PLoS ONE)
In this paper, a disaster-causing probability evaluation method of gas pipelines in karst areas based on disaster system theory and vulnerability theory is proposed. The hazard evaluation index system of gas pipeline disaster events in karst areas is established from three aspects: the activity of disaster-prone environment, the risk of disaster factors and the vulnerability of disaster-bearing bodies. Combined with the advantages of information transmission and updating of the Bayesian network model, the hazard probability of disaster events is gradually calculated from a multi-level perspective. Based on the structural reliability theory, the vulnerability evaluation function of gas pipelines in karst areas is established by considering the interaction between disaster hazard intensity and disaster resistance ability. Meanwhile, the design checkpoint method and finite element simulation are used to calculate the vulnerability probability. Finally, a new disaster-causing probability evaluation approach for gas pipelines in karst areas is formed, which comprehensively considers the event hazard and the pipeline vulnerability. The work presented in this paper can provide a reference for the safety management and accident prevention of gas pipelines crossing the karst areas.